Diamond-coated quartz crystal microbalance sensors: Challenges in high yield production and enhanced detection of ethanol and sars-cov-2 proteins - Tibor Izsák; Marian Varga; Michal Kočí; Ondrej Szabó; Kateřina Aubrechtová Dragounová; Gabriel Vanko; Miroslav Gál; Jana Korčeková; Michaela Hornychová; Alexandra Poturnayová; Alexander Kromka (Materials & Design)
This study presents the technological progress in the deposition of diamond thin films on quartz crystal microbalance (QCM) sensors. The linear antenna microwave plasma chemical vapour deposition (CVD) technique effectively grows thin diamond films on QCM substrates (Dia-QCM) differently oriented on the substrate holder in the deposition chamber, resulting in single-sided and double-sided coated QCMs. Each of these coated QCMs offers a distinctive advantage for sensing applications. The double-sided coated QCM sensors exhibited the most effective performance in ethanol detection, demonstrating approx. a 3-fold and 12-fold higher response than single-sided diamond-coated and bare gold QCM sensors, respectively. Furthermore, the single-sided Dia-QCM aptasensors demonstrated superior performance compared to bare gold QCM sensors, with a 2-fold higher response and a lower detection limit for S-RBD protein (LODDia-QCM = 0.09 pg/mL vs. LODAu-QCM = 0.10 pg/mL). In experiments conducted in human plasma, the Dia-QCM aptasensor demonstrated the ability to detect S-RBD protein at concentrations as low as 50 pg/mL, with high percentage recoveries. These results highlight the potential of linear antenna microwave plasma CVD for the mass production of advanced diamond-coated QCM sensors with different diamond film morphologies (porous, micro- or nanocrystalline) for various applications.